PENGARUH PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI DENGAN MINAT BELAJAR DAN KEPERCAYAAN DIRI SEBAGAI PEMEDIASI (STUDI PADA MAHASISWA AKUNTANSI FEB UNIVERSITAS ISLAM MALANG) - Danang Guntoro; Moh. Amin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This study aims to determine the effect of learning behavior on accounting understanding with interest in learning and self-confidence as a mediator in Accounting Students Class 2017, Faculty of Economics and Business (FEB), Islamic University of Malang. This study used primary data and the sample used in this study was 257, based on the slovin calculation, the sample obtained was 157 respondents. Questionnaires distributed as many as 157 questionnaires to respondents who are students of the Islamic University of Malang majoring. Questionnaires that did not return 0 and the number of questionnaires that were filled out incompletely were 6 respondents. So that the questionnaires that can be processed are 151.Keyword : learning behavior, level of accounting understanding, interest in learning, confidence as a mediator